The Role of Activin Receptor-Like Kinase 1 Signaling in the Pulmonary Vasculature of Experimental Diaphragmatic Hernia - Hofmann, Alejandro Daniel; Zimmer, Julia; Takahashi, Toshiaki; Gosemann, Jan-Hendrik; Puri, Prem (European Journal of Pediatric Surgery, 2016)
Aim The high morbidity and mortality in newborn infants diagnosed with congenital diaphragmatic hernia (CDH) is widely recognized to be due to pulmonary hypoplasia and persistent pulmonary hypertension (PH). The underlying structural and molecular pathomechanisms causing PH are not fully understood. Recently, activin receptor-like kinase 1 (ALK-1), an endothelial cell (EC) receptor, has been implicated in the pathogenesis of PH. ALK-1 transmits signals via a Smad pathway stimulating EC proliferation and migration leading to structural lung remodeling consecutively resulting in PH. Increased pulmonary expression of ALK-1 has been reported in patients with severe PH as well as in experimental models of PH. We designed this study to investigate the hypothesis that pulmonary ALK-1 expression is increased in nitrofen-induced CDH.Methods Pregnant rats were exposed to nitrofen or vehicle on D9. Fetuses were sacrificed on D21 and divided into nitrofen (n = 16) and control group (n = 16). Quantitative real-time polymerase chain reaction, Western blotting, and confocal-immunofluorescence microscopy were performed to determine pulmonary gene and protein expression as well as vascular localization of expressed ALK-1.Results Pulmonary gene expression levels of ALK-1 were significantly upregulated in nitrofen-treated lung tissue compared with controls. Western blotting showed increased pulmonary protein expression for ALK-1 in the CDH group when compared with control lung tissue. Confocal microscopy demonstrated markedly increased medial and adventitial thickness of pulmonary arteries in the CDH group and revealed increased ALK-1 protein expression of the pulmonary vasculature of CDH pups compared with controls.Conclusion Upregulated gene and increased protein expression of ALK-1 in the pulmonary vasculature of nitrofen-induced CDH suggest that increased expression of ALK-1 may play a crucial role in the molecular pathogenesis of vascular remodeling induced PH in experimental CDH.
Keywords: CDH; nitrofen; activin receptor-like kinase 1; pulmonary hypertension; vascular remodeling